Demand forecasting and order planning for humanitarian logistics: An empirical assessment. Issue 1 (15th July 2016) - van der Laan, Erwin; van Dalen, Jan; Rohrmoser, Michael; Simpson, Rob
Abstract: Humanitarian aid organizations are most known for their short‐term emergency relief. While getting aid items to those in need can be challenging, long‐term projects provide an opportunity for demand planning supported by forecasting methods. Based on standardized consumption data of the Operational Center Amsterdam of Médecins Sans Frontières (MSF‐OCA) regarding nineteen longer‐term aid projects and over 2000 medical items consumed in 2013, we describe and analyze the forecasting and order planning process. We find that several internal and external factors influence forecast and order planning performance, be it indirectly through demand volatility and safety markup. Moreover, we identify opportunities for further improvement for MSF‐OCA, and for humanitarian logistics organizations in general.